HER2 inhibitor-based combination therapy for recurrent and metastatic salivary duct carcinoma in an elderly patient: a case report and literature review - Zhang, Luxin; Xu, Xiaofeng; Gao, Liujie; Ding, Jiyuan (Frontiers in Oncology, 2025)
Salivary duct carcinoma (SDC) is a rare and highly aggressive malignancy with limited treatment options, particularly in elderly patients. HER2 overexpression has emerged as a potential therapeutic target in this disease. This study reports the case of an 86-year-old male with HER2-positive submandibular gland SDC who underwent surgical resection on June 19, 2020. Six months postoperatively, follow-up revealed lymph node metastasis and local recurrence at the left submandibular region. Ultrasound-guided radiofrequency ablation was performed, but local recurrence persisted. The patient subsequently received trastuzumab combined with low-dose nab-paclitaxel, achieving a partial response according to RECIST 1.1 criteria. Maintenance therapy with trastuzumab monotherapy was then initiated, resulting in disease stability for over 20 months. In October 2023, the disease progressed to the left sublingual region. After targeted monotherapy and local radiotherapy by April the following year, disease control was achieved. At the most recent follow-up, the patient remains in stable condition. This case highlights the efficacy and safety of HER2-targeted combination therapy in elderly SDC patients, offering valuable insights into biomarker-driven personalized treatment strategies for this population.